1974
DOI: 10.1139/y74-050
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Elicited by Polyethylene Glycol and Isoproterenol Reduced by Antiserum to Angiotensin II

Abstract: The effect of the infusion of antiserum to angiotensin II on extracellular thirst was studied in rats. Drinking induced by the administration of polyethylene glycol or isoproterenol was reduced significantly when antiserum was infused. These results indicate that angiotensin is involved in drinking in response to extracellular dehydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
1983
1983

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Hypovolemia causes renin release and, as noted earlier, a blockade of angiotensin's actions (Abdelaal, Mercer, & Mogenson, 1974) or ablation of the subfornical organ (Simpson et aI., 1977) reduce hypovolemic drinking by half in the rat. In their recent experiments Fitzsimons and Moore-Gillon demonstrated that acute obstruction of the venous return raised the plasma renin levels of their dogs, and that competitive inhibition of angiotensin action with infusions of Saralasin prolonged the latency of the onset of their drinking and reduced its amount.…”
Section: N Onhormonal Afferents Of Hypovolemic Thirstmentioning
confidence: 70%
“…Hypovolemia causes renin release and, as noted earlier, a blockade of angiotensin's actions (Abdelaal, Mercer, & Mogenson, 1974) or ablation of the subfornical organ (Simpson et aI., 1977) reduce hypovolemic drinking by half in the rat. In their recent experiments Fitzsimons and Moore-Gillon demonstrated that acute obstruction of the venous return raised the plasma renin levels of their dogs, and that competitive inhibition of angiotensin action with infusions of Saralasin prolonged the latency of the onset of their drinking and reduced its amount.…”
Section: N Onhormonal Afferents Of Hypovolemic Thirstmentioning
confidence: 70%
“…Systemic injections of isoprenaline cause drinking in rats (Zamboni & Siro-Brigiani, 1966;Lehr, Mallow & Krukowski, 1967;Peskar, Leodolter & Hertting, 1970;Abdelaal, Mercer & Mogenson, 1974Leenen & Stricker, 1974), and dogs (Fitzsimons & Szczepanska-Sadowska, 1974;Rolls & Ramsay, 1975). Isoprenaline J. ATKINSON AND OTHERS peripheral isoprenaline in the rat (Meyer, Peskar & Hertting, 1971;Houpt & Epstein, 1971).…”
Section: Introductionmentioning
confidence: 99%